Kinematic performance analysis of a parallel mechanism for loading test of hydraulic support. (February 2022) - Peng, Siyang; Cheng, Zhihong; Che, Linxian; Zheng, Yuwei; Cao, Shuang
Highlights: Propose a novel parallel mechanism for loading test of hydraulic support. Establish the explicit direct position solutions of this mechanism. Present the good transmission orientation workspace of this mechanism. Compare the orientation capability under different dimensional parameters. Abstract: A novel 1T2R parallel mechanism (PM), applied in loading test of hydraulic support, is proposed, whose kinematic performance is studied in detail. The analytical expression of forward kinematic positions are derived by means of vector method. With the aid of Jacobian matrix, the singular configurations are investigated. The orientation capacity of end-effector is depicted through the azimuth and tilt angles. Using screw theory as the mathematical tool, this paper establishes the evaluation indices for motion/force transmission performance such as input transmission index, output transmission index and local transmission index (LTI). The definitions and calculation methods of good transmission orientation workspace (GTOW), regular transmission orientation workspace, and average transmission index in regular workspace are presented, respectively. Furthermore, the distributions of GTOW and the surface of LTI are plotted. Finally, the analysis results indicate that PU-RPU-UPS PM has good kinematic performances, which can be used as loading actuator of the new hydraulic support test-bed.